Gambaran Empty Nest Syndrome (ENS) Pada Lanjut Usia dI UPT Tresna Werdha Kabupaten Jember - Susanto, Tantut; Prasetyo, Ananto Adi; Kurdi, Fahruddin; Fauziah, Wahyuni (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2024)
Introduction: Empty Nest Syndrome (ENS) is at risk for the elderly who are separated from their children, especially those who live in Tresna Werdha Social Care institutions. This study aimed to describe the overview of ENS experienced by the elderly in Tresna Werdha Social Care institutions, Jember Regency Methods: The research design used is a descriptive survey. The sampling technique used is total sampling. The sample used in this study was 72 elderly who were selected based on inclusion and exclusion criteria. Data were collected using the Empty Nest Syndrome questionnaire to measure the overview of ENS in elderly. Data analysis was performed by one sample Kolmogorov-smirnov with a significance level of 0.05. Results: The result showed that there was no significant difference in the level of empty nest syndrome but in the high category (Md (P₂₅-P₇₅)= 114,0 (108,0-120,75); Z= 0,080; p-value 0,200). Majority respondents got high level of ENS with a total of 38 respondents (52,8%). Conclusion: This study concludes that empty nest syndrom ENS remains relatively high in erderly. However, elderly people who stay more than 1 year experience low ENS.